Islamic Thought Offers in the Polemic of Fanaticism Religious Communities in Indonesia - Achmad Tohari (Westscience Press, 2024)
This research aims to look at offers in inter-religious dialogue in Indonesia regarding the polemic of religious fanaticism. This research explains the Islamic thought approach of Nurcholis Madjid and Amin Abdullah using analytical descriptive methods which include qualitative research with data in the form of literature and journals that are still related to the theme. The data collection technique is a literature study that relies on the books Islam, Modernity and Indonesianness from Nurcholis Madjid and Religious Studies: Normativity or Historicity from Amin Abdullah and related journals. The findings achieved from this research are in the form of an understanding of the ideas of historicity, normativity and religious inclusivism which explains that all three have the same approach in creating peace in Indonesia. historicity with historical, anthropological and sociological approaches, both of which must be united to be able to see the diversity of Indonesian society. Nurcholis Madjid with the idea of inclusivism, he criticizes religious traditions which tend to be formalistic textualists, thus changing them with a normative-historical approach and a classical-modern approach to be contextualized in the diversity of Indonesia's pluralistic society. It can be seen that these two Islamic thinkers have contributed ideas that can be actualized for the continuation of peace between religious communities in Indonesia. Therefore, both of them have approaches that can be used in dialogue between religious communities as an offer to polemics about religious fanaticism in Indonesia.